2006
DOI: 10.1007/s10562-006-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature selective catalytic reduction of NO by NH3 over V2O5 supported on TiO2–SiO2–MoO3

Abstract: The V 2 O 5 catalysts supported on TiO 2 -SiO 2 -MoO 3 (TSM) prepared by the coprecipitation method were investigated for the selective catalytic reduction (SCR) of NO by NH 3 at low temperatures. The V 2 O 5 /TSM catalyst with 7-13 wt% SiO 2 was found to exhibit a superior SCR activity and a good sulfur tolerance at low temperatures (<250°C). The presence of highly active polymeric vanadates formed by the incorporation of MoO 3 to TiO 2 -SiO 2 and superior redox properties seems to enhance SCR activity, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…6,75,76 The catalytic performance was further promoted by loading V2O5 on a TiO2-SiO2-MoO3 support using co-precipitation method. 77 This catalyst exhibited a superior SCR activity and a good sulfur tolerance at lower temperature. Such superior lowtemperature SCR activity was mainly attributed to the presence of polymeric vanadate species and high redox property besides high surface area.…”
Section: V2o5-based Catalystsmentioning
confidence: 99%
“…6,75,76 The catalytic performance was further promoted by loading V2O5 on a TiO2-SiO2-MoO3 support using co-precipitation method. 77 This catalyst exhibited a superior SCR activity and a good sulfur tolerance at lower temperature. Such superior lowtemperature SCR activity was mainly attributed to the presence of polymeric vanadate species and high redox property besides high surface area.…”
Section: V2o5-based Catalystsmentioning
confidence: 99%
“…6 Choo et al found that BaO on a V 2 O 5 /TiO 2 catalyst significantly suppresses SO 2 oxidation by reducing the redox ability of vanadium oxide on the catalyst surface and the adsorption capacity of SO 2 . [8][9][10] A few fundamental studies have been performed on the mechanism of SO 2 oxidation over V 2 O 5 /TiO 2 based catalysts. [8][9][10] A few fundamental studies have been performed on the mechanism of SO 2 oxidation over V 2 O 5 /TiO 2 based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have been made to promote low-temperature SCR performance of vanadia catalysts through the use of promoters such as 1%CrO 3 -6%V 2 O 5 /TiO 2 [3] and 1%MO x (M = Fe, Mn, Cu or Cr)-3%V 2 O 5 /mesoporous carbon-coated monoliths [6]. Other approaches have changed the support to materials such as 3-8%V 2 O 5 /carbon-coated monoliths [7][8][9] [13], 3-7%VO x (x < 2.5)/TiO 2 (supports obtained from different companies) [14]. However, these catalysts were unable to reduce the vanadia loading.…”
Section: Introductionmentioning
confidence: 99%